A Multiobjective and Fast Optimization Algorithm for Wearable Antenna Array Design - Choudhury, Suvadeep; Costa, Filippo; Manara, Giuliano; Tedjini, Smail; Genovesi, Simone (IEEE transactions on antennas and propagation, 2025)
This study introduces a computationally efficient technique for a fast but reliable evaluation of the radiation characteristics of antennas placed in a complex environment. The method is based on scattering matrix representation of the addressed antenna system as a basis to retrieve both the near-field and the far-field variations in correspondence to the selected points of interest. The effectiveness of the proposed approach is demonstrated through different test cases that include various kinds of radiators such as dipoles, loops, and planar-inverted folded antennas (PIFAs). Due to its computational efficiency, the method is adopted to design a suitable feeding scheme of a wearable antenna array to achieve the desired level of near-field and radiated fields by using a multiobjective algorithm. Furthermore, the Complex Antenna Factor (CAF) is defined and exploited to generalize the estimate of the near-field in the case of proximity to multilayered dielectric objects.